(untitled) (Journal of Human Sciences, 2022)
Selling is considered as one of the important financial transactions that are indispensable for a Muslim. It is one of the daily practices that a person carries out. Selling of Murabaha (making profit) to order buying is of these practices. Such types of selling have recently spread as alternative to an interest-based loan. Therefore, this research has a great importance. The researcher works to present the accurate judgments for this type of sale, and correct the misconceptions about it. The researcher also highlights the difference between it and the sale of absolute Murabaha. This research aims to acquaint traders in this sale with the rules and the conditions that verify the validity of this sale. It becomes something that a Muslim will be rewarded for, and also ensuring that rich people will not abuse poor people who are in need. Therefore, the research problem lies in finding a legitimate reason in order for such type of selling would be accepted by Shareha (Islamic law) providing that the two parties are content. In order for the researcher to be able to reach to such results, he will use the inductive and prognostic approach to reach the judgments that expand the circle of the lawful to the acceptance of Allah and His Messenger. One of the most important results of this research is that the Murabaha sale to the person ordering the purchase has two equal opinions, and are permissible for every Muslim to adopt one of them according to his condition, circumstance and degree of faith.